2020
DOI: 10.1108/ilt-06-2020-0204
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behaviors of the water-lubricated rubber bearings under different lubricated conditions

Abstract: Purpose This study aims to evaluate the tribological behavior of water-lubricated rubber bearings sliding against stainless steel under different lubricate conditions. Design/methodology/approach The water-lubricated rubber bearings under various normal loads and sliding speeds were carried out on the ring-block friction test, and the wear morphology is test conducted by using scanning electron microscope. Findings The results indicate that the surface of water-lubricated rubber bearings has a more alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Xiao et al [254] pointed that the surface of waterlubricated rubber bearings has a more alternative friction coefficient and wear rate under seawater than in other lubrication conditions. The seawater not only acts as a lubricating medium but also brings microstructure while corroding the rubber interface, thereby further enhancing the lubricating effect and storing abrasive debris.…”
Section: Lubrication In Space or Marinementioning
confidence: 99%
“…Xiao et al [254] pointed that the surface of waterlubricated rubber bearings has a more alternative friction coefficient and wear rate under seawater than in other lubrication conditions. The seawater not only acts as a lubricating medium but also brings microstructure while corroding the rubber interface, thereby further enhancing the lubricating effect and storing abrasive debris.…”
Section: Lubrication In Space or Marinementioning
confidence: 99%
“…Water-based lubricants are widely used in bearings and seals that operate in aqueous environments. 1 Due to growing environmental concerns, attempts have been made in recent years to replace traditional oil-based lubricants with environmentally friendly water-based lubricants. 2,3 However, compared with lubricating oils, the low viscosity and poor filmforming ability of water severely limit the performance and dependability of water lubrication systems.…”
Section: Introductionmentioning
confidence: 99%
“…Water-based lubricants are widely used in bearings and seals that operate in aqueous environments . Due to growing environmental concerns, attempts have been made in recent years to replace traditional oil-based lubricants with environmentally friendly water-based lubricants. , However, compared with lubricating oils, the low viscosity and poor film-forming ability of water severely limit the performance and dependability of water lubrication systems. , To solve these problems, water-soluble oils, emulsions, ionic liquids, and nanomaterials are widely used as additives in water-based lubricants. In addition, carbon-based solid lubricating coatings, such as diamond-like carbon (DLC), silicon-incorporated DLC (Si-DLC), and various metal-doped DLC (Me-DLC), have great potential in water lubrication systems and could effectively solve issues of high friction, high wear, cavitation, and corrosion .…”
Section: Introductionmentioning
confidence: 99%
“…Prominent studies on the subject in the literature are as follows: Liu et al presented a new water-lubricated rubber bearing model for vibrating operations [1]. Ixiao et al examined the tribological behaviour of water-lubricated rubber bearings sliding against stainless steel [2]. Zhou et al investigated the straight-groove or spiral-channel Stribeck curve of WLRB with NR material in a comparison experiment using the rotational speed and external load as variables and found that the friction coefficient of straight-groove WLRB decreased with an increase in the load over the entire speed range [3].…”
Section: Introductionmentioning
confidence: 99%